Hydrocortisone with fludrocortisone for septic shock: a systematic review and meta‐analysis. Issue 1 (1st September 2020) - Yamamoto, Ryo; Nahara, Isao; Toyosaki, Mitsunobu; Fukuda, Tatsuma; Masuda, Yoshiki; Fujishima, Seitaro
Abstract : Aim: Combined hydrocortisone and fludrocortisone therapy for septic shock has not been evaluated with an independent systematic review. We aimed to elucidate the beneficial effects of a dual corticosteroid treatment regime involving both hydrocortisone and fludrocortisone for adult patients with septic shock on mortality. Methods: We searched the Medline, Cochrane CENTRAL, and ICHUSHI databases for reports published before April 2019. We included randomized controlled trials that compared the use of both hydrocortisone and fludrocortisone with either corticosteroid‐free or hydrocortisone‐only treatments on adult patients with septic shock. Three researchers independently reviewed the studies. The meta‐analyses were undertaken to assess primary outcome (28‐day mortality) and secondary outcomes (in‐hospital mortality, long‐term mortality, shock reversal, and adverse events). Results: Among the four studies eligible for data synthesis, we included 2, 050 patients from three studies for quantitative synthesis. All studies used similar regimens (hydrocortisone and fludrocortisone for 7 days without tapering). The 28‐day mortality rate was reduced after dual corticosteroid treatment (risk ratio, 0.88; 95% confidence intervals [CI], 0.78–0.99). The heterogeneity between the studies was low ( I 2 = 0%). Patients who underwent dual corticosteroid treatment had lower long‐term mortality rates (risk ratio, 0.90; 95% CI, 0.83–0.98) and higher rate of shock reversal after 28 days (odds ratio, 1.06; 95% CI, 1.01–1.12) than control patients. Adverse events (except for hyperglycemia) were similar among the treatment groups. Conclusions: The available evidence suggests that a combination of fludrocortisone and hydrocortisone is more effective than adjunctive therapy and could be recommended for septic shock. Abstract : A systematic review and meta‐analysis were carried out on randomized controlled trials of a dual corticosteroid treatment with both hydrocortisone and fludrocortisone for adult patients with septic shock. Hydrocortisone and fludrocortisone treatment reduces the 28‐day mortality of patients with septic shock with minimum risk of adverse events. The pathophysiological mechanisms of the additional fludrocortisone and the duration of treatment should be further studied.